Managers view on impact of Covid-19 pandemic: evidence from hotel industry in Malaysia - Ghazali, Hazrina; Ishak, Maisarah (Macrothink Institute, 2021)
2020 is an important year which had been waiting for by the hotel industry in Malaysia. With the exciting slogan “Visit Truly Asia Malaysia,” Malaysia was aimed by many to be one of the most chosen countries to be visited. This simultaneously gives a high hope to the hotel industry to generate more revenues. However, the COVID-19 pandemic has changed the hotel industry landscape tremendously. Therefore, the purpose of this research is to explore the impact of COVID-19 on the hotel industry in Malaysia. This study employed qualitative method and six hotel representatives were participated in this study. The interview data revealed experiences, voices, and opinions of the hotel informants on the impact of COVID-19. The informants also shared their immediate strategies and long-term plans in coping with the pandemic. In addition, the informants also shared information on the Tourism Stimulus Package offered by the Government that they have received.